(untitled) (San Diego, CA., 2000)
factors that govern the behaviour of the same organisms, together with an analysis of likely outcomes of microbial growth/metabolism in terms of disease and/or spoilage. The book also describes the contribution of microorganisms to industrial fermentations, to traditional food fermentations from the Middle or Far East, as well as during the production of the fermented foods like bread, cheese or yoghurt that are so familiar in industrialized societies
Keywords: Food; Microbiology